2011
DOI: 10.1186/1471-2164-12-289
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of heat-responsive small RNAs derived from the chloroplast genome of Chinese cabbage (Brassica rapa)

Abstract: BackgroundNon-coding small RNAs play critical roles in various cellular processes in a wide spectrum of eukaryotic organisms. Their responses to abiotic stress have become a popular topic of economic and scientific importance in biological research. Several studies in recent years have reported a small number of non-coding small RNAs that map to chloroplast genomes. However, it remains uncertain whether small RNAs are generated from chloroplast genome and how they respond to environmental stress, such as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 46 publications
(57 reference statements)
3
80
0
Order By: Relevance
“…This is in agreement with the presence of numerous tRFs deriving from plastid tRNAs in Brassica napa (8). These tRFs are formed by cleavage in positions very similar to those found for nuclear tRFs.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the presence of numerous tRFs deriving from plastid tRNAs in Brassica napa (8). These tRFs are formed by cleavage in positions very similar to those found for nuclear tRFs.…”
Section: Discussionsupporting
confidence: 89%
“…Many chloroplast-derived sRNAs (csRNAs) have recently been identified. 3234 We took advantage of the available barley chloroplast genome sequence to distinguish between sRNAs derived from the chloroplast and nuclear genomes in barley and found that about one-fourth of sRNAs were derived from the chloroplast genome in both P-deficient and P-sufficient shoots (Table 1). In contrast to sRNAs derived from the nuclear genome, csRNAs were highly redundant in both P treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some new candidate miRNAs were observed to be organelle-derived miRNAs (Additional file 1: Table S10), which suggested that these miRNAs were derived by alternative biogenesis pathways, not via Dicer proteins. Indeed, sRNAs can be generated from organelles including chloroplasts and mitochondria in animals, plants, fungi and humans [33-36]. New candidate miRNAs are considered to be young miRNAs that have evolved recently, and are often expressed at a lower level than conserved miRNAs, as reported from Arabidopsis and Triticum [37,38].…”
Section: Discussionmentioning
confidence: 99%